Noninvasive brain stimulation combined with other therapies improves gait speed after stroke: a systematic review and meta-analysis. Issue 3 (3rd April 2019) - Vaz, Patricia Graef; Salazar, Ana Paula da Silva; Stein, Cinara; Marchese, Ritchele Redivo; Lukrafka, Janice Luisa; Plentz, Rodrigo Della Méa; Pagnussat, Aline Souza
ABSTRACT: Background : Repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) are noninvasive brain stimulation (NIBS) techniques able to modulate cortical excitability. Objective : To determine the effects of NIBS combined with other therapies on gait speed after stroke. Methods : Electronic databases searched were PUBMED, EMBASE, COCHRANE, SCOPUS, SCIELO and PEDro. Eligibility criteria were randomized controlled trials that reported the effects of tDCS and rTMS combined with other therapies for improving gait speed, walking cadence, functional ambulation category (FAC) and motricity index (MI-LE) after stroke. Risk of bias was assessed by Cochrane risk of bias assessment tool. Mean differences (MD) and 95% confidence intervals were calculated. Quality of evidence was assessed by Grades of Researches, Assessment, Development and Evaluation approach. Results : Ten studies (226 subjects) were included in the meta-analysis. NIBS combined with other therapies was effective for improving gait speed (MD 0.09 m/s [95% CI, 0.05 to 0.13; I 2 0%, p < 0.0001]). Gait speed improved in both acute/subacute (MD 0.08 m/s [95% CI, 0.02 to 0.14]) and chronic phases (MD 0.08 m/s [95% CI, 0.03 to 0.13]). Furthermore, inhibitory (MD 0.09 m/s [95% CI, 0.04 to 0.14]) and excitatory (MD 0.07 m/s [95% CI, 0.02 to 0.12]) protocols were effective to improve gait speed. NIBS was also effective to improve walking cadence but was unable to modify other outcomes (FAC and MI-LE). Conclusions : This systematic review with meta-analysis synthesizes moderate-quality evidence that NIBS combined with other therapies are effective to improve gait speed after stroke. Systematic Review registration number : PROSPERO registration number CDR42015024237.